Report of the Working Group on Movement of Foodgrains and Fertilisers by Rail - Planning Commission (Planning Commission Government of India, 1970)
The report by the Planning Commission’s Working Group outlines a strategic framework for the efficient rail movement of foodgrains and fertilisers in India. Highlighting current transport patterns, the report identifies challenges such as prolonged transit times, cross movements, and strain on rail capacity, particularly during scarcity periods. For the Fourth Plan (1969–74), it projects substantial transport requirements for fertilisers and foodgrains and recommends enhancements in rolling stock, line capacity, terminal facilities, and storage infrastructure. Long-term projections emphasize continued growth in agricultural outputs, necessitating ongoing logistics optimization, coordinated ministry action, and mechanized port handling to ensure food security and transport efficiency.
Government of India Planning Commission March 1970
Keywords: Foodgrains Transport; Fertilisers Movement; Rail Capacity; Logistics Optimization; Freight Planning; Fourth Five Year Plan; Storage Facilities; Rolling Stock Augmentation; Port Handling; Agricultural Supply Chain; Transit Efficiency; Transport Infrastructure